STRATEGI PENINGKATAN PENGETAHUAN PENDIDIDKAN AGAMA ISLAM MELALUI KONTEN YOUTUBE PADA MAHASISWA KEDOKTERAN UNIVERSITAS ABULYATAMA ACEH - Ilham, Ilham; Winarty, Asih; Saifuddin, Saifuddin; Usman, Usman; Akhyar, Akhyar (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Islamic Religious Education (PAI) plays a significant role in shaping the character of medical students who have a busy academic schedule. However, conventional learning often faces problems such as lack of student interest and limited time to attend classes optimally. This suggests the need for innovative strategies that can address the needs of the digital generation. This study aims to explore the effectiveness of YouTube media as an alternative to learning PAI that is interactive, flexible, and in accordance with the needs of medical students at Abulyatama University Aceh. The researcher used a mixed-method research method involving 120 students who were divided into two groups: experimental and control. Data were collected through pre-test and post-test and supported by surveys and interviews. The experimental group was given PAI learning using YouTube video content designed according to the curriculum while the control group used conventional methods. The research data were analysed using paired sample t-test statistical test to evaluate the difference in learning outcomes between the two groups. The results showed that the experimental group experienced a significant increase in post-test scores with an average of 83.14 compared to the pre-test of 66.11, while the control group only experienced a small increase from 65.05 to 70.22. The significant difference proved that YouTube media was able to improve the understanding of PAI concepts more effectively than conventional methods. Students also stated that YouTube media provides flexibility in learning time and is more interesting than traditional learning. Thus, this study illustrates that the integration of technology in PAI learning to answer educational problems, in addition, using YouTube as a learning media can be a strategic alternative in a more effective learning process for students with busy academic schedules.